1. THE RETENTION STRATEGY FOR MEDICAL DOCTORS AT COMMUNE HEALTH STATIONS: USING DISCRETE CHOICE EXPERIMENTS IN TUYEN QUANG AND THAI BINH IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: The article analyzes the influencing factors and impact levels of retention strategy packages for medical doctors at CHSs. Methods: Direct survey was conducted with 118 doctors working at CHSs in Tuyen Quang and Thai Binh during May, 2023. Using discrete choice experiments to analyze the impact of the retention strategy packages for medical doctors at CHSs. Result: The findings show that income is a priority factor in choosing a workplace for doctors participating in the survey, in which increasing the occupational incentive allowance is the most effective attribution. If occupational incentive allowance was increased to 100% and 140%, the proportion of doctors who will choose to work at CHSs is 95.8% and 98.2%, respectively. When there is no incentive to increase income, 74.8% of doctors will choose to work at CHSs if the working condition is ensured in terms of equipment and medicines, and 58.4% of doctors if the job has incentives for the health insurance of relatives. Conclusion: Thus, in order to retain health workers working at the CHSs, policies need to be reviewed and consider these options to ensure human resources for the healthcare level as well as to strengthen the medical network in Vietnam
Keywords: Doctors, retention, commune health station, primary health care, Vietnam.